Atributos químicos da solução e do solo após aplicação de resíduo da extração de celulose - Maciel, Thais M. S. [UNESP]; Alves, Marlene C. [UNESP]; Silva, Flavia C. (Univ Federal Campina Grande, 2015)
The purpose of the study was to evaluate, under greenhouse conditions, using soil columns and cycles of wetting, the effect of residues from the extraction of cellulose on the chemical composition of the soil solution and on the two Red Oxisols. The experimental design was completely randomized. The treatments were: T1 - without the addition of lime and residue (control), T2 - 1.0 t ha(-1) of limestone, T3 - 1.2 t ha(-1) dregs/grits, T4 - 0.8 t ha(-1) of lime mud; T5 - 2.4 t ha(-1) ash, T6 - 1.8 t ha(-1) dregs/grits + lime mud + ash in the ratio 1: 3: 6, T7 - 1.0 t ha(-1) dregs/grits + lime mud in the ratio 1:3. Evaluation was performed of the chemical composition of the solution extracted from each soil during four months of incubation and also chemical analysis of soil thereafter. The results were analysed by performing analysis of variance and Tukey test for comparison of means at 0.05 probability level. Among the applied treatments, 1.2 t ha(-1) dregs/grits is not found suitable for use in soil because of larger concentration of Na+ transferred to the soil solution than recommended in the literature and the 2.4 t ha(-1) ash treatment can be used as a source of K to the soil.

Este trabalho objetivou avaliar, em casa de vegetação e usando colunas de solo e ciclos de umedecimento, o efeito da aplicação de resíduos da extração de celulose sobre a composição química do solo e da solução extraída de dois Latossolos Vermelhos. O delineamento experimental utilizado foi inteiramente casualizado. Os tratamentos utilizados foram: T1 - Sem adição de calcário e resíduo (testemunha); T2 - 1,0 t ha-1 de calcário calcítico; T3 - 1,2 t ha-1 de dregs/grits; T4 - 0,8 t ha-1 de lama de cal; T5 - 2,4 t ha-1 de cinza; T6 - 1,8 t ha-1 de dregs/grits + lama de cal + cinza na proporção 1:3:6; T7 - 1,0 t ha-1 de dregs/grits + lama de cal na proporção 1:3. A avaliação da composição química da solução extraída de cada solo estudado, foi realizada durante quatro meses de incubação e análises químicas do solo, após este período. Os resultados foram analisados efetuando-se a análise de variância e o teste de Tukey para as comparações de média no nível de 0,05 de probabilidade. Dentre os tratamentos aplicados o 1,2 t ha-1 de dregs/grits pode não ser adequado para utilização no solo visto que transferiu maior concentração de Na+ para a solução do solo em relação ao recomendado pela literatura enquanto o tratamento 2,4 t ha-1 de cinza pode ser utilizado como fonte de K ao solo.
Chemical attributes of the solution and soil after application of residue of cellulose extraction
Keywords: Oxisol; Ashes; Dregs/grits; Potassium; Sodium